2010
DOI: 10.1186/1477-7525-8-93
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, reliability and validity of health-related quality of life questionnaire among adult pulmonary tuberculosis patients in urban Uganda: cross-sectional study

Abstract: BackgroundDespite the availability of standard instruments for evaluating health-related quality life (HRQoL), the feasibility, reliability, and validity of such instruments among tuberculosis (TB) patients in different populations of sub-Saharan Africa where TB burden is of concern, is still lacking.ObjectiveWe established the feasibility, reliability, and validity of the Medical Outcomes Survey (MOS) in assessing HRQoL among patients with pulmonary tuberculosis in Kampala, Uganda.MethodsIn a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 12 publications
7
45
2
Order By: Relevance
“…The validation study from Taiwan [27] used WHOHRQOL -BREF (World Health Organization Health Related Quality of Life-BREF) also showed an adequate reliability. However, only one HRQOL instrument showed cross culture adaptability [26].…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The validation study from Taiwan [27] used WHOHRQOL -BREF (World Health Organization Health Related Quality of Life-BREF) also showed an adequate reliability. However, only one HRQOL instrument showed cross culture adaptability [26].…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…In this review, all kinds of TB patients pulmonary TB, extra pulmonary TB, active TB disease, late TB infection, current TB and recurrent TB were included. The methodology quality of six studies [15,23,26,27,37,39] was validated by the use of COSMIN check list and results were demonstrated on the scale from poor to excellent (Tables 5 and 6). None of these studies included the measurement error while one study showed cross cultural validity [26] measures mostly focused on perceptions which are subjective and without a gold standard.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations